Designing a digital portfolio - Baron, Cynthia (Voices that matter., 2010)
From the Publisher: Portfolios have always been artists' most valuable tools for communicating their talents to the outside world, whether to potential employers or galleries or clients. But the days of sketches and slides have given way to arrangements of digital assets that are both simpler and more complex than their traditional analog counterparts. Instructor and design professional Cynthia Baron covers all the facets that artists need to know, from choosing the best work for a particular audience to using various file formats to organizing, designing, and presenting the portfolio. Beautiful full-color illustrations demonstrate her instructions and case studies throughout portray examples of attractive and effective portfolio design. This book gives artists at any level a creative edge, ensuring that their portfolios get noticed and help them stand out from the crowd.